Disease-specific quality of life following a flare in systemic lupus erythematosus: an item response theory analysis of the French EQUAL cohort. (17th October 2019) - Corneloup, Marie; Maurier, François; Wahl, Denis; Muller, Geraldine; Aumaitre, Olivier; Seve, Pascal; Blaison, Gilles; Pennaforte, Jean-Loup; Martin, Thierry; Magy-Bertrand, Nadine; Berthier, Sabine; Arnaud, Laurent; et al.
Abstract: Objective: To explore, at an item-level, the effect of disease activity (DA) on specific health-related quality of life (HRQoL) in SLE patients using an item response theory longitudinal model. Methods: This prospective longitudinal multicentre French cohort EQUAL followed SLE patients over 2 years. Specific HRQoL according to LupusQoL and SLEQOL was collected every 3 months. DA according to SELENA-SLEDAI flare index (SFI) and revised SELENA-SLEDAI flare index (SFI-R) was evaluated every 6 months. Regarding DA according to SFI and each SFI-R type of flare, specific HRQoL of remitting patients was compared with non-flaring patients fitting a linear logistic model with relaxed assumptions for each domain of the questionnaires. Results: Between December 2011 and July 2015, 336 patients were included (89.9% female). LupusQoL and SLEQOL items related to physical HRQoL (physical health, physical functioning, pain) were most affected by musculoskeletal and cutaneous flares. Cutaneous flares had significant influence on self-image. Neurological or psychiatric flares had a more severe impact on specific HRQoL. Patient HRQoL was impacted up to 18 months after a flare. Conclusion: Item response theory analysis is able to pinpoint items that are influenced by a given patient group in terms of a latent trait change. Item-level analysis provides a new way of interpreting HRQoL variation in SLE patients, permitting a better understanding of DA impact on HRQoL. This kind of analysis could be easily implemented for the comparison of groups in a clinical trial. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT01904812.